2015
DOI: 10.1155/2015/613584
|View full text |Cite
|
Sign up to set email alerts
|

Herbal SGR Formula Prevents Acute Ethanol-Induced Liver Steatosis via Inhibition of Lipogenesis and Enhancement Fatty Acid Oxidation in Mice

Abstract: Our previous study indicated that herbal SGR formula partially attenuates ethanol-induced fatty liver, but the underlying mechanisms remain unclear. In the present study, mice were pretreated with SGR (100 and 200 mg/kg/d bw) for 30 d before being exposed to ethanol (4.8 g/kg bw). The biochemical indices and histopathological changes were examined to evaluate the protective effects and to explore potential mechanisms by investigating the adiponectin, tumor necrosis factor-α (TNF-α), peroxisome proliferators-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…In the current acute alcohol binge administration study, the degrees of hepatic lipid accumulation and lipid peroxidation did not vary between WT and SHP-KO mice. Previous studies have demonstrated that chronic and acute alcohol-induced steatosis may share a common mechanism responsible for the upregulation of lipid biosynthesis and lipid oxidation, which involves sterol regulatory element-binding protein 1 in fatty acid synthesis and AMP-dependent protein kinase, peroxisome proliferator-activated receptor (PPAR)α and adiponectin in lipid oxidation ( 33 , 38 40 ). To the best of our knowledge, although the underlying mechanisms responsible for the phenotypic differences resulting from alcohol-associated hepatic steatosis are largely undetermined, based on the inconsistent degrees of hepatic lipid accumulation between acute and chronic alcohol administered SHP-KO mice, it may be hypothesized that the role of SHP in hepatic lipid metabolism may vary between acute and chronic alcohol ingestion conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In the current acute alcohol binge administration study, the degrees of hepatic lipid accumulation and lipid peroxidation did not vary between WT and SHP-KO mice. Previous studies have demonstrated that chronic and acute alcohol-induced steatosis may share a common mechanism responsible for the upregulation of lipid biosynthesis and lipid oxidation, which involves sterol regulatory element-binding protein 1 in fatty acid synthesis and AMP-dependent protein kinase, peroxisome proliferator-activated receptor (PPAR)α and adiponectin in lipid oxidation ( 33 , 38 40 ). To the best of our knowledge, although the underlying mechanisms responsible for the phenotypic differences resulting from alcohol-associated hepatic steatosis are largely undetermined, based on the inconsistent degrees of hepatic lipid accumulation between acute and chronic alcohol administered SHP-KO mice, it may be hypothesized that the role of SHP in hepatic lipid metabolism may vary between acute and chronic alcohol ingestion conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In another research, Qiu et al () investigated the effects of a triple mixed herbal formulation named SGR on fatty liver developed by chronic ethanol consumption. This formulation consists of three herbs: Semen Hoveniae extract: 80%, GBLE: 10%, and Rosa roxburghii Tratt extract: 10%.…”
Section: Chemical Toxicitiesmentioning
confidence: 99%
“…Findings of this study represented that ethanol elevated the triglyceride level in serum and liver tissue of mice through the decreased expression level of adiponectin, peroxisome proliferator‐activated receptor (PPAR‐α) and AMPK‐β, and increased expression level of TNF‐α and sterol regulatory element binding protein 1c (SREBP‐1c). SGR administration for 30 days had the potential of regulating the expression of adiponectin, PPAR‐α, TNF‐α, SREBP‐1c, and the level of phosphorylated AMPK‐β, instead of the total expression of AMPK‐β (Qiu et al, ). In the studies, which are conducted on a combination of several herbs, there is an uncertainty in making conclusion about the effects of every herbal component, unless some treated groups with the isolated or purified herbal extracts are added.…”
Section: Chemical Toxicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol, even in the form of BD, is known to affect SIRT1 as it decreases the NAD+/NADH ratio, on which SIRT1 is dependent 16 . On the other hand, different works establish that alcohol decreases the phosphorylation and activation of AMPK [17][18][19][20] . It seems that during the oxidation of NADH, produced by the metabolism of alcohol, energy generated is used to synthesize ATP; therefore, the AMP/ATP ratio is decreased and AMPK inhibited 21 .…”
Section: Introductionmentioning
confidence: 99%